Banca electrónica y la satisfacción del cliente en una institución financiera de Iquitos 2024 - Sanchez Cabrera, Almendra Melita (2025)
The objective of this research work was to determine how electronic banking and customer satisfaction are related in a financial institution in Iquitos 2024. The study is of a basic type, with a quantitative approach with a non experimental cross-sectional design. The sample consisted of 100 clients. In this study, the survey and the questionnaire were used as instruments. In the results it could be observed that, out of a total of 100 respondents in Electronic Banking and Customer Satisfaction in a Financial Institution in Iquitos 2024, 4.0% responded that they never use electronic banking in a Financial Institution in Iquitos 2024, therefore, 6.0% commented that almost never, in addition 21.0% stated that sometimes, on the other hand, 28.0% expressed that almost always, meanwhile, 41.0% stated that they always use electronic banking in a Financial Institution in Iquitos 2024. Concluding that there is a significant relationship between electronic banking and customer satisfaction in a financial institution in Iquitos in the year 2024, they confirm that financial institutions that invest in the development and constant improvement of their digital platforms generate a positive impact on their customer base. This approach not only improves the perception of the service, but also fosters a more accessible and inclusive environment, suited to the needs of urban and rural communities.